Hematological Parameters, Biochemical Findings and Cerebrospinal Fluid Profiles among Guillan-Barre Syndrome Patients - Islam, Md. Zakirul; Ara, Anjuman; Yusuf, Md. Abdullah; Karim, Rezaul; Hussain, Mohammad Enayet; Moureen, Adneen; Shaikh, Merazul Islam (Journal of Current and Advance Medical Research, 2025)
Background: Laboratory parameters are very important among Guillain-Barré Syndrome patients. Objective: This study was undertaken to assess the hematological, biochemical, and cerebrospinal fluid profiles among patients with Guillain-Barré Syndrome. Methodology: This cross-sectional study was conducted from October 2017 to September 2018 in the Department of Clinical Neurology at the National Institute of Neurosciences and Hospital, Dhaka, Bangladesh. The patients were selected according to the selection criteria and after confirmation by an electrophysiological study. Details of laboratory profiles of the study population were collected, like hematological, biochemical, and cerebrospinal fluid parameters. Details history and meticulous examination were performed to collect the data according to the variable of interest. All necessary investigations were done at an optimum time. Results: A total of 108 GBS patients were recruited for this study. The mean age of patients with the demyelinating subtype was 40.20 ± 16.26 years, while that of the axonal subtype was 32.43 ± 14.93 years (p = 0.011). The mean hemoglobin (Hb) level was slightly lower in the demyelinating subtype (12.75 ± 1.98 g/dL) compared to the axonal subtype (13.19 ± 1.69 g/dL) (p = 0.213). The mean ALT value was notably higher in the axonal subtype (53.01 ± 36.95 U/L) compared to the demyelinating subtype (38.67 ± 19.27 U/L) (p = 0.012). The mean CSF cell count was nearly identical in both groups, with 2.50 ± 0.92 cells/mm³ in the demyelinating subtype and 2.55 ± 0.95 cells/mm³ in the axonal subtype (p = 0.784). The CSF glucose concentration was also comparable between the two subtypes, showing a mean of 4.23 ± 1.44 mmol/L in the demyelinating group and 3.91 ± 0.86 mmol/L in the axonal group (p = 0.178). In contrast, the CSF protein concentration showed higher mean values in the demyelinating subtype (418.28 ± 499.40 mg/L) compared to the axonal subtype (278.09 ± 488.82 mg/L) (p = 0.153). Conclusion: In conclusion, there are several laboratory parameters that are statistically significantly different between axonal and demyelinating types of GBS. Journal of Current and Advance Medical Research, July 2024;11(2):88-96